Accumulation of degree days and their effect on the potential yield of 15 eggplant (Solanum melongena L.) accessions in the Colombian Caribbean - Rommel Igor León Pacheco (Revista Facultad Nacional de Agronomía Medellín, 2019)
The growing degree-days (GDD) provide an estimate of the accumulated thermal energy available for the development of a crop. The use of GDD allows measuring the heat requirements associated with the phenological stages of the crop, which allows in turn, to predict when a certain plant stage will occur knowing the daily temperatures. The aim of this study was to establish relationships among the effect of degree days (DD) to vegetative growth, first flowering and fructification (VG, Fl and Fr), on total yield per plant (TY/P) of eggplant grown under open-field conditions employing a randomized complete block design with 15 genotypes and four replicates. The results showed that: 1) The genotypes that initiated fruit production in less time required fewer GDD (892.14-1,077.71 °C) for this phenological phase, obtaining higher productivity. 2) The genotypes C035 and C040 had an average yield higher than the national average with values of 83.75 and 84.86 t ha-1, being identified as future varieties to be produced in the Caribbean region. 3) The Caribbean region is suitable for the establishment of the crop as there were no events with limiting temperatures for this species (higher than 35 °C and lower than 15 °C). 4) The principal component analysis showed associations among the variable YT/P with the genotypes C011, C042, and C015; meanwhile, C032, C025, and C028 were associated with the variables DD to VG, Fl, and Fr. These results would be useful in developing a model to estimate yield with DD.